STORMWATER CONTROL MEASURES TO REDUCE URBAN STORMWATER AND NUTRIENT INPUTS TO BOATHOUSE CREEK, NORTH CAROLINA - Bond, Ryan (East Carolina University, 2019)
Portions of the lower White Oak River and surrounding waters in Carteret County, NC are nutrient-sensitive. Over the last few decades, land surrounding Boathouse Creek, a tributary of the lower White Oak, has experienced an increase in development, impervious surfaces, and runoff. Stormwater runoff has been identified as the primary contributor of non-point source pollution to local surface waters. The goal of this study was to characterize the overall water quality of Boathouse Creek under baseflow and stormflow conditions and reduce the volume of runoff and associated pollutants entering Boathouse Creek through the use of stormwater control measures (SCMs). In May of 2015, monitoring and sampling of surface waters at eight locations within the Boathouse Creek watershed was initiated and continued for approximately one year. Monthly monitoring included pH, temperature, dissolved oxygen, oxidation-reduction potential, specific conductance, turbidity, and stream stage and flow measurements. Samples were analyzed quarterly for total dissolved nitrogen (TDN), ammonium (NH4-N), nitrate (NO3-N), and phosphate (PO4-P). Stable isotopic analyses ([delta]15N and [delta]18O) of NO3-N from surface waters were also conducted to determine potential sources of NO3-N. SCMs were implemented from July to September of 2016, with monitoring and sampling resuming after implementation for approximately six months. Similar methods and analyses were also used for six storm events. Dissolved oxygen concentrations were below the state standard ([greater-than or equal-to]5.0 mg/L daily average) on approximately 30% of the occasions sampled. Nutrient analyses showed relatively low mean concentrations of TDN (<1.0 mg/L) and phosphate (<0.02 mg/L) during baseflow conditions, and increased concentrations of TDN during storms. Dissolved organic nitrogen was found to be the dominant form of nitrogen in Boathouse Creek and the primary cause for elevated storm TDN concentrations. Isotopic analyses indicated that the most likely sources of NO3-N in surface waters are waste material from humans/animals and soil organic matter. Compared to pre-SCM site estimates, runoff was reduced by 258,000 L for the regional 1-year, 24-hour storm event. Annually, approximately 3,800,000 L of runoff was prevented from entering Boathouse Creek, while nitrogen and phosphorus loading was reduced by approximately 2.5 kg-N/ha/yr and 0.1 kg-PO4-P/ha/yr, respectively. More research is needed to better understand SCM performances in the NC Coastal Plain, but future work could help refine these estimates. Continued efforts to reduce stormwater runoff related pollution are suggested to improve water quality. Additionally, because human and/or animal waste was identified as a nitrogen source in Boathouse Creek, future efforts should also focus on reducing waste-related nitrogen inputs, including loading from onsite wastewater treatment systems.
Keywords: nutrients; Urban runoff--North Carolina--Carteret County; Information storage and retrieval systems--Water quality